Photosynthetic biocathode enhances the power output of a sediment‐type microbial fuel cell - AS Commault; G Lear; P Novis; RJ Weld (New Zealand Journal of Botany, 2014)
Conventional microbial fuel cells (MFCs) consist of biological anodes and abiotic cathodes separated by a proton‐exchange membrane. The abiotic cathode usually catalyses the reduction of oxygen to produce water by means of expensive catalysts such as platinum. 1 The cathodic reaction is often limiting in MFCs and researchers are now focusing on efficient, low‐cost catalysts to improve oxygen reduction at the cathode. This paper describes a photosynthetic biocathode in a sediment‐type MFC constructed without a proton‐exchange membrane. The carbon and stainless steel cathode did not contain any catalyst, but was covered in a biofilm composed of a complex community including microalgae and cyanobacteria. Although electroactive species were detected in the cathode biofilm, no biocatalysis of oxygen reduction was observed. Enhancement of the current output was mostly due to the production of pure oxygen near the cathode surface by the photosynthetic biofilm. Photosynthesis could produce dissolved oxygen levels approximately four times higher than oxygen levels obtained by aeration. The MFC was able to generate a maximum power density of 11 mW/m 2 (projected anode area) over six months without feeding.